(untitled) (Ameghiniana, 2013)
The present paper includes detailed descriptions and illustrations of four gastropod species: Knightites (Cymatospira) montiortianus (Norwood and Pratten); Glabrocingulum (Ananias) sp.; Neilsonia? sp.; and Peruvispira umariensis? (Reed). All of them are recorded for the first time in Argentina and indicate an Upper Carboniferous to Lower Perrnian age for this Formation.